Development of an Online, Culturally Responsive, Accelerated Language Arts Curriculum for Middle School Students. Issue 3 (July 2023) - Robins, Jennifer H.; Sanguras, Laila Y.; Carpenter, Ashley Y.
In this article, we focus on two components of the Online Curriculum Consortium for Accelerating Middle School (OCCAMS) project: the curriculum frameworks and the curriculum development process. The frameworks include the Integrated Curriculum Model (advanced content, unit themes, and process/product), culturally responsive curriculum, and talent development. In our discussion of the curriculum frameworks, we share how two accelerated, online courses centered on themes that motivate and engage diverse learners: identity, heroism, conviction, and sacrifice. In addition, we highlight how the exploration of these themes through texts written by diverse authors and featuring diverse characters allows students to go on an even deeper journey into self-discovery. The second focus of this article is on the curriculum development process. We illustrate the iterative nature of the development of the curriculum, including descriptions of the site visits and use of teacher and student feedback in each stage of revisions.